Descriptive epidemiology of clinically significant occupational poisonings, United States, 2008–2018. (2nd December 2021) - Downs, John W.; Wills, Brandon K.; Cumpston, Kirk L.; Rose, S. Rutherfoord
Abstract: Introduction: References listing common occupational poisons often include agents that were observed decades prior to the introduction of worker protective laws and regulations. Current causes of work-related acute poisonings have not been characterized. This study's primary objective was to describe the most common poisons and routes of exposure responsible for clinically significant occupational poisonings. A secondary objective was to determine the crude rate of clinically significant occupational poisonings and occupational poisoning-related deaths over the study period. Methods: This was a retrospective cohort study using electronic data from the American Association of Poison Control Centers' (AAPCC) National Poison Data System (NPDS), and open source data from the United States Bureau of Labor Statistics (BLS). The NPDS was queried for all cases with exposure reason coded as "Unintentional-Occupational" for the period 1 January 2008 to 31 December 2018. A case of clinically significant occupational poisoning (CSOP) was defined as a case with moderate or severe clinical effects reported, to include fatal cases. A descriptive analysis was conducted using unadjusted odds ratios to assess the strength of association between main variables of interest and CSOP. Results: 329, 437 exposure cases were available for analysis. Of these, 54, 254 were considered CSOP and included 196 deaths. The top five poisons responsible for occupational fatalities were hydrogen sulfide, ammonia, carbon monoxide, simple asphyxiants, and chlorines. Fatalities were 3.7 times (OR: 3.7; 95% CI: 2.2–6.4) more likely to be men and 5.7 times (OR: 5.7; 95% CI: 4.0–8.1) more likely to have had an inhalational exposure, compared to those workers with CSOP without fatality. The crude rate of occupational fatal poisoning reported to US poison centers was 11.3 deaths per 100, 000, 000 worker-years during the study period. The crude rate of clinically significant occupational poisoning was 3.1 per 100, 000 worker-years. These rates remained generally stable over the study period. Conclusion: Occupational poisonings continue to be a significant cause of morbidity and mortality in the workplace despite significant improvements in workplace chemical safety over the last four decades. Workplace education and proper preventive measures devoted to inhalational toxicants and respiratory protection are opportunities for improvement.